Peduli Kualitas Kesehatan Masyarakat Setempat Dengan Cegah Stunting - Agfirlila, Ainun Salsya; Khairunisah, Luluk; Astrina, Meyla; Tantry, Sriwerinda; Ananta, Puti; Setiawan, Robi; Fatimah, Fatimah; Dwi Rachmi, Inieke; Rohim, Abdul; Sholihin, Fernando (Universitas Gajah Putih, Indonesia, 2023)
Linear growth failure or as ussually known as stunting is undernutrition problem globally. It is happen in childhood with physical and neurocognitive damage that accompanies stunted growth characterictic. Indonesia as developing country currently trying to solve this problem through government programs. The aims is to improve the quality of young generation. From the results of the Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting in Indonesia is 21.6% in 2022. This high percentage is also supported by poor access to health care in living rural areas. Kampung Sialang Baru also like that. Where it was recorded that this village had poor access to health care. Beside that, the village got the second ranked in most of stunting children in Lubuk Dalam district. There are 18 childs who were infected. This is the result of observations made by Kukerta team. They made socialization stunting program and provide information leaflets about MPASI. The socialization went slowly bring good impact. The participants gained knowledge about MPASI is on of the important thing to prevent stunting. Also, they have leaflets as source of detail information of MPASI menu that is suitable for children.